Investigation of research issues in cloud computing - Ren, Zhi Ping (2014)
Cloud computing refers to the use of computing resources (hardware and software) that are delivered as a service over the Internet. Cloud computing relies on sharing of resources to achieve coherence and economies of scale similar to a utility over the Internet. Cloud computing is especially attractive to business owners as it eliminates the need for users to plan ahead for provisioning, and allows enterprises to start from small and increase resources only when there is a rise in service demand.